Literature Review: Peran Digital Mindfullness dalam Pencegahan Quiet Quitting pada Sistem Kerja Hibrida - Yeski Putri Utami; Firasy Aldrin H; Khairun Niswaharsa (ARZUSIN, 2026)
The development of hybrid work systems has provided flexibility for companies but has also generated digital pressure, blurred boundaries between work and personal life, and increased psychological fatigue, all of which contribute to the emergence of quiet quitting, a condition in which employees perform only the minimum required tasks without displaying additional enthusiasm or engagement. This study aimed to identify the factors that cause quiet quitting, analyze the influence of hybrid work systems on the escalation of this behavior, and propose digital mindfulness strategies as a preventive effort. The research employed a literature study method, with the collected sources analyzed thematically to identify patterns and relationships among concepts. The analysis shows that quiet quitting is triggered by high digital pressure, blurred work–life boundaries, burnout, unhealthy organizational culture, lack of managerial support, and an imbalance between workload and rewards. Hybrid work systems amplify these triggering factors by demanding near-constant connectivity and reducing individual control over digital workload. Organizational efforts such as flexibility policies or well-being programs are deemed insufficiently effective because they do not directly address individual habits and self-management. Digital mindfulness, understood as the ability to use technology consciously and purposefully, is identified as an important strategy for managing digital distractions, maintaining focus, and enhancing work engagement, which can be strengthened through clear work policies, boundaries for digital communication, education on attention management, and the establishment of realistic work expectations. Overall, digital mindfulness offers an individually grounded approach that is both promising and effective in preventing quiet quitting in hybrid work environments.